The Use of Dyadic Essay Technique to Increase Speaking Skills in Senior High School Surakarta - Oktavia, Masitoh (Universitas PGRI Semarang, 2025)
The research investigates the implementation of Dyadic Essay Technique (DET) as an instructional strategy to improve speaking skills among senior high students in Surakarta. While DET is primarily used to improve writing skills, this study explores its adaption for speaking activities through collaborative questions generation and peer discussions. A Classroom Action Research (CAR) design was used involving 30 of the eleventh-grade students in one private senior high school in Surakarta. Data collection method was observation, oral performance assessments, student’s journal, and interviews. The findings reveal that Dyadic Essay Technique fosters better engagement, confidence, and speaking fluency by promoting meaningful dialogue and peer feedback. Moreover, students reported increased motivation and engagement due to the interactive and peer-supported nature of the technique. The researcher suggests that incorporating DET into speaking instruction can effectively support language development in communicative contexts. Further researchers may also consider using DET in improving another English language skill like reading and writing prior to see its broader applicability)